Experimental and Simulation Investigation of Performance of Scaled Model for a Rotor of a Savonius Wind Turbine - Al-Gburi K.A.H.; Al-quraishi B.A.J.; Ismail Alnaimi F.B.; Tan E.S.; Al-Safi A.H.S. (MDPI, 2023)
Aerodynamics; Computational fluid dynamics; Potential energy; Turbine components; Turbomachine blades; Wind; Wind power; Wind turbine blades; CFX analyse; Coefficient of power; Condition; Experimental testing; Performance; Renewable energy source; Rotor experimental testing; S-ORM model; Savonius wind turbine; Scaled modeling; Wind tunnels